Antioxidant activity and phenolic content of different parts of Orthosiphon stamineus grown under different light intensities - Mohd Farhan, Abd Razak; Abd. Razak, Shaari; Pin, Kar Yong; Luqman Chuah, Abdullah, Prof. Dr. (Forest Research Institute Malaysia, 2013)
Link to publisher's homepage at http://www.frim.gov.my/